Overcoming barriers? The mixed results of social innovation accelerator programs for women entrepreneurs - Dutt, Nilanjana; Kaplan, Sarah (Strategic Management Journal, 2026)
Abstract Research Summary Entrepreneurship accelerators are increasingly promoted as structural interventions to close gender gaps, yet studies have not established a differential impact of participation for women. This prior evidence—drawn from high‐tech, male‐dominated settings—may overlook how outcomes differ in more feminized domains such as social innovation. Using unique multi‐level data from 1417 ventures applying to 33 accelerators, we examine whether average effects conceal variation across institutional environments and program designs. We find that in more gender‐egalitarian countries, women‐led ventures performed better than peers after participating, especially in programs aiming to support women. In less egalitarian environments, however, participation offered negative or no such advantages even in gender supportive programs. These results suggest that well‐intended interventions to advance women entrepreneurs are context‐dependent and may sometimes reinforce the very disparities they intended to diminish. Managerial Summary Social innovation accelerators are often championed as a way to help women entrepreneurs thrive. But our analysis of 1417 ventures applying to 33 programs shows that results vary—and context matters. In more egalitarian countries, participation is associated with improved performance for women‐led ventures, especially when programs are explicitly designed to support them. Surprisingly, the pattern flips in less egalitarian environments: women founders who join even women‐focused programs often see no performance gains—or even declines—relative to peers. These findings suggest that well‐intentioned support can backfire if it doesn't fit the local institutional environment. For program designers and leaders, this is a call to move beyond one‐size‐fits‐all approaches and carefully align equity goals with the realities of the ecosystems they operate in.